Changes in physicochemical properties and antioxidant activity of fermented kepayang (Pangium edule Reinw.) seeds - Mustaffer, Nur Hafizah; Ramli, Nurul Shazini; K., Tongkhao; K., Vangnai; N. K., Rosni; Rukayadi, Yaya (Rynnye Lyan Resources, 2021)
One method for processing Pangium edule Reinw. seeds for consumption is fermentation. The aim of this study was to determine the physicochemical characteristics of P. edule Reinw. seeds during fermentation and antioxidant activity of the extracts. P. edule Reinw. seeds were boiled for 2 hrs and subjected to spontaneous fermentation for 40 days. The physicochemical properties were evaluated according to AOAC methods. Raw and fermented P. edule Reinw. seeds (day 40) were dried and extracted using ethanol and distilled water. The antioxidant activity was measured using 2,2-diphenyl-1- dipicrylhydrazyl (DPPH) radical scavenging assay while total phenolic content was measured by following the Folin-Ciocalteu method. The results showed that there were no significant differences in water activity while the pH value was decreased along fermentation days. The TSS was significantly increased from day 0 (11.00) to day 30 (19.50), however, it drastically decreased to 11.50 after 40 days of fermentation. The value of lightness (L*) parameter was decreased from 66.44 to 25.28 on day 40 but no significant differences for a* and b* parameter. For proximate analysis, the percentage of ash, crude protein, crude fat, and crude fibre were significantly increased while moisture content and carbohydrate were significantly decreased throughout the fermentation days. Besides, the highest DPPH activity was observed in the ferment-water extract at concentration 10 mg/mL which about 95.61% while the highest total phenolic content was obtained from the ferment-ethanol extract (173.79 mg GAE/100 mg). In conclusion, there were some changes in the physicochemical properties of P. edule Reinw. seeds during fermentation and potentially has antioxidant activities. The results of this study might be used as basic information to develop the fermented seeds as a functional food.